2019
DOI: 10.11114/jets.v6i12a.3952
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-efficacy on Performance of Sports Skills of Football Players

Abstract: The main goal of this study was to determine effect of self-efficacy on performance of football players in Erzurum city. The present research was practical in terms of purpose and correlation in term of its nature. The statistical population of research was Ataturk University boys students (18-22 yrs old) unfamiliar to football scissors kick, in 2018. So, 52 participants were selected randomly based on Morgan Table from 60 volunteers. In this study, two questionnaires of self-efficacy and Charbonneau sport per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
2
6
1
Order By: Relevance
“…The positive relationship between sports success and self-efficacy was confirmed in the study. The results of this study are consistent with previous research performed among athletes [11][12][13][14][15][16][17][18][19][20][21][22][23], as well as in the domains of physical activity [5][6][7][8][9][10][11] and academic achievements [3,4]. According to theory [1,2], people with a high sense of self-efficacy do not give up due to difficulties, treat such situations as an opportunity to master the task, and believe in learning from failures [68].…”
Section: Association Between Self-efficacy Bas and Sports Successsupporting
confidence: 93%
“…The positive relationship between sports success and self-efficacy was confirmed in the study. The results of this study are consistent with previous research performed among athletes [11][12][13][14][15][16][17][18][19][20][21][22][23], as well as in the domains of physical activity [5][6][7][8][9][10][11] and academic achievements [3,4]. According to theory [1,2], people with a high sense of self-efficacy do not give up due to difficulties, treat such situations as an opportunity to master the task, and believe in learning from failures [68].…”
Section: Association Between Self-efficacy Bas and Sports Successsupporting
confidence: 93%
“…Research findings revealed that the self-efficacy component of PsyCap in middle and high school baseball players had a positive impact on player performance (β = 0.13, p < 0.05). These findings were consistent with previous studies that reported self-efficacy contributes to competitive player performance [48,49]. Self-efficacy is a major concept in social cognitive theory, which posits that individuals can be viewed as self-organizing, proactive, self-reflecting, and self-regulating [14].…”
Section: Self-efficacy and Player Performancesupporting
confidence: 92%
“…In their study, they concluded that self-efficacy has a significant impact on the athletic performance of professional ski jumpers. Also, the results of the study conducted by Sivrikaya (2019) show that self-efficacy has an influence on the athletic performance of football players, in other words, self-efficacy is one of the most important characteristics of a successful athlete.…”
Section: Discussionmentioning
confidence: 99%
“…Athletic self-efficacy is defined as the athlete's belief in the ability to perform a successful operation to achieve a specific outcome in athletic performance. On the one hand, athletic self-efficacy includes the athlete's abilities, physical and mental fitness, leadership and coaching, and situational superiority, and on the other hand, it influences the athletic performance, success, and the ability to cope with stress (Sivrikaya, 2019).…”
Section: Introductionmentioning
confidence: 99%